Mechanism Of Action Of A Benzimidazole Sirtuin Inhibitor, Bzd9l1, In Colorectal Cancer - Tan, Yi Jer (2022)
Sirtuins (SIRTs) are NAD+-dependent deacetylases that is implicated in various epigenetic diseases including cardiovascular and neurodegenerative diseases, diabetes, aging and cancer. The emergence of SIRTs as therapeutic targets and limitations of existing SIRT inhibitors led to the discovery of a novel SIRT inhibitor: BZD9L1. As testing of the effects of BZD9L1 on the enzymatic activities of SIRTs have been hampered by the availability of commercial kits, BZD9L1 interactions on SIRTs were studied using molecular modelling and docking studies. Molecular docking studies revealed that BZD9L1 may bind to SIRT1-3, 6 and 7 with similar confirmation but with different affinities, thereby expanding the therapeutic potential of BZD9L1 in metabolic diseases. In addition, in silico approaches were deployed to further elucidate BZD9L1-modulated mechanisms based on existing experimental data. In silico analysis of BZD9L1-regulated targets showed that the proliferation and apoptosis of HCT 116 cells may be due to p53-dependent signalling pathways. BZD9L1 was found to be effective against different cancer cell lines especially colorectal cancer (CRC), where its first-line chemotherapy regimen 5-fluorouracil (5-FU) often result in treatment failure due to drug insensitivity and severe side effects. As current efforts to overcome these boundaries involved sensitizing tumours through adjuvant treatments, this project also aims to provide novel insights into the potential development of BZD9L1 as an adjuvant to 5-FU in CRC therapy using in vitro and in vivo models. The combination of BZD9L1 and 5-FU was found to be more effective against HCT 116 CRC cell line in reducing cell viability and survival compared to sole treatment via synergistic effect.